2017
DOI: 10.1016/j.jsps.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of community pharmacists about the risks of medication use during pregnancy in central region of Saudi Arabia

Abstract: Community Pharmacists are the most accessible health care providers who can help pregnant women with their medications use there are still gaps in knowledge where educational interventions are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 10 publications
2
27
1
2
Order By: Relevance
“…One study was conducted in Riyadh, Buraydah and Hail, one in Riyadh and Jeddah and one in Riyadh, Jeddah, Makkah and Madina . Majority of studies were questionnaire‐based surveys . Five studies used simulated patient methodology, while two studies used face to face interview and questionnaire‐based survey as their evaluation method .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study was conducted in Riyadh, Buraydah and Hail, one in Riyadh and Jeddah and one in Riyadh, Jeddah, Makkah and Madina . Majority of studies were questionnaire‐based surveys . Five studies used simulated patient methodology, while two studies used face to face interview and questionnaire‐based survey as their evaluation method .…”
Section: Resultsmentioning
confidence: 99%
“…Community pharmacist's knowledge and practices of pharmaceutical care were evaluated by two studies . There were five studies which targeted specific areas of pharmaceutical care like community pharmacist's knowledge attitude and practices to provide medication counselling and patient education in oral health, herbal products, pregnancy and mental illnesses . All studies included in this review represented community pharmacist's knowledge, role, attitude and professional practices towards the patient‐centred care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some patients approach pharmacists as the first step in seeking medical advice for their symptoms (13). Furthermore, studies have identified pharmacists as a primary health care provider in answering drug-related queries and counselling pregnant women on their medications (13,14).…”
Section: Introductionmentioning
confidence: 99%